Sodium Bicarbonate (NaHCO3) Affects The Growth of Microalgae Chlorella sp - Junda, Muhammad; Rahmat, Awal Nur; Daud, Firdaus; Kurnia, Nani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study aims to determine the effect of adding sodium bicarbonate (NaHCO3) on the growth of microalgae. This study was an experimental study using a completely randomized design (RBD) which had 4 treatments and 1 control with 3 repetitions each. The four ingredients for adding sodium bicarbonate had different concentrations, namely 50 ppm, 100 ppm, 150 ppm and 200 ppm while the Control did not add sodium bicarbonate. Following the Anova analysis technique at a confidence level of α < 0.05, the research data were subjected to Duncan's advanced test using the SPSS statistical software. The results of the study show that the growth of Chlorella sp. microalgae is affected by the addition of sodium bicarbonate (NaHCO3). This is based on the results of measurements of biomass with the highest average value found in treatment A (addition of sodium bicarbonate NaHCO3 50 ppm) of 2.319 g/L compared to the control average value of 1.819 g/L, different from the results of the chlorophyll-a content obtained there was no effect on the control, where the highest average value of chlorophyll content was 1.459986mg/mL from the control (K) and the lowest average was 0.937614 mg/mL from treatment C.